INFLUENTIAL FACTORS IN MATHEMATICAL PERFORMANCE OF THE UNAC ENGINEERING STUDENT - Author (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The present investigation aims to know the factors involved in the academic performance in mathematics of engineering students at the National University of Callao to improve the teaching-learning process and raise the quality of graduates. Therefore, by operationalizing the independent variable, factors such as: The same student entered the University, the teacher who teaches mathematics during the first five academic semesters of the curriculum, the academic performance is analyzed, the report notes of the minutes of the courses of mathematics and of the determining factors are complemented with the question question of the regular students of the faculty on the aspects of the matter, teacher and personnel, included of the Academic Year 2016 to 2019, it was demonstrated the existing relationship Between the factors, the performance and the academic performance of the student through the Chi-square for a confidence level of 95%. Some activities are proposed to achieve the participation of the family in the school performance of students in order to help improve their school performance.